Design of a broadband circularly polarised uniplanar crossed-dipole antenna - Wang, Heesu; Park, Yong Bae; Park, Ikmo (Scientific Reports, 2024)
This study presents the design of a uniplanar crossed-dipole antenna with broadband characteristics. The antenna comprises a pair of identical crossed-dipole arms printed on the same plane of a dielectric substrate. The crossed-dipole arms are corner-cut fat dipoles that are perpendicular to each other and connected with a bent stripline to generate circularly polarised (CP) radiations. A wide dipole arm was used to improve impedance matching and widen the axial ratio (AR) bandwidth. Additionally, the corner of each dipole arm was cut into a triangular shape to broaden the impedance and AR bandwidths further. The antenna in free space is excited via a wideband microstrip-to-parallel stripline tapered balun to reduce the effect of leakage current on the coaxial cable. Experiments and full-wave electromagnetic simulations were employed to design, verify, and validate the antenna design. The antenna, having an overall size of 45 × 45 × 0.508 mm3 (0.4 × 0.4 × 0.0045 λL3 where λL is the lowest frequency in the 3-dB AR bandwidth), demonstrates the following measured performances: an |S11|< − 10 dB impedance bandwidth of 2.53–9.14 GHz (113.3%), a 3 dB AR bandwidth of 2.65–7.75 GHz (98.1%), and peak gain of 3.7 dBic at 6.6 GHz.